Uji Efektivitas Daun Bungur (Lagerstroemia speciosa L.) terhadap Penghambatan Transportasi Glukosa Tikus Putih Galur Wistar (Rattus norvegicus) - Haryanto Haryanto; Muhammad Halim Ramadhan; Rifdah Rifdah; Dian Indra Aulia; Harianti Harianti; Nadia Azzahra (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This study investigated the effects of bungur leaves containing saponins, flavonoids and tannins on glucose and cholesterol levels in rat (Rattus norvegicus) test animals. Spectrophotometry results showed a significant decrease in glucose levels at different concentrations. SPSS analysis indicated that the data were normally distributed, and comparison of average glucose levels between treatment groups showed similar homogeneity. The significant value of bungur obtained was 0.014 < 0.05 from the ANOVA test, strengthening the conclusion that bungur leaves can contribute to glucose control which aims to increase the potential of active compounds contained in bungur samples in inhibiting blood glucose absorption.